Analysis of the tribological performances of biodegradable hydraulic oils HEES and HEPR in the sliding of Cu–Zn/WC–CoCr alloys using the Stribeck curve - Castro, Richard de Medeiros (2020)
In surface engineering, new coatings and deposition techniques for decreasing wear have been proposed. However, the tribological behaviors of these coatings under lubricated sliding with biodegradable oils are unknown. The objective of this study was to evaluate the tribological behaviors of two hydraulic biodegradable oils, namely hydraulic environmental ester oil synthetic (HEES) and hydraulic oil environmental polyalphaolefn (HEPR), with hydraulic mineral oil (HLP), using a pin-on-disk tribometer. In the sliding tests, a Cu–35Zn sphere against a fat surface is coated with WC–10Co4Cr alloy using a HVOF thermal spray. The Stribeck curve was used to evaluate the performances of the lubricants. The coefcient of friction, the contact pressure, and the flm thickness were determined. In addition, the coefcient of wear of the sphere was evaluated, and the oil with the lowest value was identifed, which was HEPR in this case. In long-term tests, HEPR was afected by the stick–slip phenomenon, which increased the coefcients of friction and wear. Furthermore, the mechanism of adhesion of the sphere on the disk was more evident with the use of HEES compared to HLP. The highest concentrations of Zn and P and the pressure–viscosity coefcient value, which was detected in the mineral oil, caused friction reduction and lower damage to the surfaces. Therefore, it is important to evaluate the tribological conditions of synthetic bio-lubricants for applications in hydraulic systems.